Is Foreign Portfolio Investment Beneficial to India’s Balance of Payments? An Exploratory Analysis - GEORGE, Justine (Theoretical and Practical Research in Economic Fields; Vol 7 No 1 (2016): TPREF, Volume VII, Issue 1(13), Summer 2016DO - 10.14505/tpref.v7.1(13).01, 2016)
As oppose to the expectation, financing of Balance of Payments (BoP) with foreign investment exerted huge cost on India’s BoP. Dividend and capital gain are found to be the two cost of FPI on BoP, in which latter would considered as cost on BoP only if it is repatriated. Foreign portfolio investment (FPI) earns huge capital gain as compared to dividend and has significant evidence for repatriation